(untitled) (Jurnal Teknologi (Sciences & Engineering), 2017)
Typically, a mineral based oil from petroleum refining has been widely used as automatic transmission fluid (ATF) in the wet clutch application. However, it has two major disadvantages: (1) It causes pollution to the environment and (2) It is a non-renewable source. Thus, Palm Fatty Acid Distillate (PFAD) is explored as an alternative lubricant for the wet clutch application. In present study, tribological behaviour of PFAD is first sought using a pin on disk tribo-tester and then its behavior will be compared with the behavior obtained in the commercial ATF. It is found in the friction analysis that PFAD has good anti friction ability at low speeds. In addition, PFAD generates almost identical dynamic friction coefficients obtained in the commercial ATF at velocity of 0.4m/s to 0.9 m/s. A slight positive slope in the friction coefficientâ€“velocity graph indicates that PFAD has tendency to have anti-shudder properties, which can improve engaging quality of the wet clutch. However, PFAD has two weaknesses; low viscosity index and less anti wear ability. Some additives should be added into PFAD so that it can give better friction level and less wear rate.Â